2011
DOI: 10.1007/s12298-011-0071-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of impact of solar UV components on growth and antioxidant enzyme activity in cotton plant

Abstract: A field experiment was conducted to study the impact of solar UV-B (280-315 nm) and UV-A (315-400 nm) components on the growth and antioxidant enzyme activity in cotton plant (Gossypium hirsutum var. Vikram). Solar UV components were excluded by filtering the sunlight through selective UV-B (<315 nm) and UV-B/A (<400 nm) absorbing polyester films. Plants grown under filters that transmitted solar UV served as controls. Exclusion of UV-B and UV-B/A enhanced plant height, leaf area and total biomass of plants. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…In particular, differences in light intensity between the two environments likely influenced the relative contributions of NAR and SLA to RGR. Additional differences in environmental conditions such as the influence of wind (Baker et al, 2009), the effect of ultraviolet light (Dehariya et al, 2011), and the need for investment in defense-related metabolites (Olson et al, 2008;Nix et al, 2017) are also known to influence plant growth and could have contributed to the differences observed between the greenhouse and field conditions. In previous studies, similar results were found in that RGR differences were ascribed only to NAR (Eagles, 1967;Pons, 1977), only to LAR (Higgs and James, 1969;Dijkstra, 1989;Smeets and Garretsen, 1986), or to both NAR and LAR together (Jarvis and Jarvis, 1964;Corrẽ, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, differences in light intensity between the two environments likely influenced the relative contributions of NAR and SLA to RGR. Additional differences in environmental conditions such as the influence of wind (Baker et al, 2009), the effect of ultraviolet light (Dehariya et al, 2011), and the need for investment in defense-related metabolites (Olson et al, 2008;Nix et al, 2017) are also known to influence plant growth and could have contributed to the differences observed between the greenhouse and field conditions. In previous studies, similar results were found in that RGR differences were ascribed only to NAR (Eagles, 1967;Pons, 1977), only to LAR (Higgs and James, 1969;Dijkstra, 1989;Smeets and Garretsen, 1986), or to both NAR and LAR together (Jarvis and Jarvis, 1964;Corrẽ, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Loveys et al (2002) studied 16 different plant species including trees, shrubs, grasses, and forbs and reported that under moderate (23°C) or high temperatures (28°C), SLA was the most important factor affecting RGR, whereas at lower temperature (18°C), NAR was the more important determinant of RGR. Additional differences in environmental conditions such as the influence of wind (Baker et al, 2009), the effect of ultraviolet light (Dehariya et al, 2011), and the need for investment in defense-related metabolites (Olson et al, 2008;Nix et al, 2017) are also known to influence plant growth and could have contributed to the differences observed between the greenhouse and field conditions. Additional research would be necessary to ascertain the reasons underlying the environmental effects observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of leaf growth by solar UV and a drastic enhancement in the area of leaves after the exclusion of UV has been observed in plants such as cotton (Dehriya et al 2011) and Amaranthus (Sharma and Guruprasad 2009). The number and the area of rosette leaves were enhanced by the exclusion of UV in WT Arabidopsis also.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to UV-B has a number of detrimental effects on plants, notably, alterations in plant morphology, growth, and development such as reduction in leaf area, reduced stem growth (Cuadra et al 2004 ;Dehariya et al 2011 ;Frohnmeyer and Staiger 2003 ), decreased fl owering, and alteration in the timing of fl owering in certain species of plants. However, variations are seen in the morphological parameters depending on the plant variety and exposure time (Sakalauskaite et al 2013 ).…”
Section: Effect Of Uv-b On Plants and Their Damage Control Mechanismsmentioning
confidence: 99%